Strategi Satuan Polisi Pamong Praja dalam Penerapan Program Unggulan Kota Padang “Revitalisasi Pantai” melalui Satgas Pengamanan - Syahrani Indah Putri; Putri Febri Wialdi (Lembaga Yasin AlSys, 2026)
The Beach Revitalization Program is one of the flagship programs of the Padang City Government aimed at creating an orderly, safe, comfortable, and competitive tourist area. However, its implementation continues to face illegal parking, unofficial levies, public order disturbances, and low public compliance with regulations, thereby requiring a more effective security strategy. This study aimed to analyze the strategy of the Padang City Satuan Polisi Pamong Praja through the Security Task Force in implementing the Flagship Beach Revitalization Program and to identify the constraints encountered in its implementation. The study employed a qualitative method with a descriptive approach. Informants were selected through purposive sampling, while data were collected through interviews and documentation. The data were analyzed using Richard P. Rumelt’s strategy theory, which comprises diagnosis, guiding policy, and coherent actions. The results showed that the Padang City Satpol PP had implemented a strategy by identifying various problems in the Padang Beach area, implementing security policies based on Padang City Regional Regulation No. 1 of 2025 concerning Public Peace and Order, and undertaking coherent actions in the form of routine patrols, field supervision, enforcement against violations, and coordination with the Tourism Office. Nevertheless, the strategy had not been implemented optimally because of low public compliance, the continued occurrence of illegal parking and unofficial levies, the extensive area requiring supervision, limited personnel, difficulties in identifying violators, and suboptimal public participation in submitting reports. This study concluded that the Satpol PP strategy implemented through the Security Task Force had supported the Beach Revitalization Program, but its effectiveness still required strengthened human resources, improved interagency coordination, and active public involvement. These findings provide practical implications for the local government in developing a more integrated, participatory, and sustainable security system for tourist areas.